Conformational motion of the ABC transporter MsbA induced by ATP hydrolysis. - Peter P Borbat (Public Library of Science (PLoS), 2007)
We measured the amplitude of conformational motion in the ATP-binding cassette (ABC) transporter MsbA upon lipopolysaccharide (LPS) binding and following ATP turnover by pulse double electron-electron resonance and fluorescence homotransfer. The distance constraints from both methods reveal large-scale movement of opposite signs in the periplasmic and cytoplasmic part of the transporter upon ATP hydrolysis. LPS induces distinct structural changes that are inhibited by trapping of the transporter in an ATP post-hydrolysis intermediate. The formation of this intermediate involves a 33-A distance change between the two ABCs, which is consistent with a dimerization-dissociation cycle during transport that leads to their substantial separation in the absence of nucleotides. Our results suggest that ATP-powered transport entails LPS sequestering into the open cytoplasmic chamber prior to its translocation by alternating access of the chamber, made possible by 10-20-A conformational changes.